Long-Term Outcomes of Coronary Artery Bypass Grafting in Patients with Reduced Left Ventricular Myocardial Contractility: Single-Center Experience - Kashchenko, Yurii V.; Chekh, Khrystyna O.; Rudenko, Anatoliy V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Coronary artery bypass grafting (CABG) is one of the most effective methods for treating ischemic heart disease (IHD) in patients with multivessel coronary artery disease and significantly reduced left ventricular ejection fraction (LVEF ≤ 35%). Patients with low LVEF are considered high-risk due to an increased likelihood of cardiac complications and the limited effectiveness of alternative treatments, such as medical therapy or stenting. CABG not only reduces the risk of heart failure but also significantly improves quality of life and long-term survival, which is particularly important for this patient category. Due to its ability to fully restore myocardial blood supply even in complex clinical cases, CABG remains the standard of care for patients with severe forms of IHD. Additional findings indicate that CABG improves cardiac function and reduces the incidence of heart failure symptoms, leading to enhanced patient quality of life. Aim. To evaluate early and long-term outcomes of CABG in patients with reduced left ventricular myocardial contractility. Materials and methods. The study included 210 patients with LVEF ≤ 35%, who underwent CABG at the National Institute of Cardiovascular Surgery named after M.M. Amosov, National Academy of Medical Sciences of Ukraine, from January 1, 2015, to December 31, 2021. Patients were divided into three groups according to their LVEF: 35–У ре30%, 29–25%, and ≤ 24%. An analysis was conducted on the changes in ejection fraction, end-diastolic volume, and clinical symptoms at the time of hospitalization, discharge, and one year after surgery. Results. The study results showed that CABG in patients with LVEF ≤ 35% was associated with significant improvement in left ventricular ejection fraction and reduction of clinical symptoms. The most significant improvement was observed in the group of patients with LVEF ≤ 24%. Conclusions. Coronary artery bypass grafting in patients with low ejection fraction (≤35%) significantly reduces clinical symptoms (chest pain, dyspnea, edema), improves cardiac function with an increase in ejection fraction, prevents further EF reduction, and substantially decreases end-diastolic index in patients with initial EDI >100 ml/m², demonstrating a positive effect on left ventricular remodeling.